Economic Plants of Tripura State VII. Plants Used for Manufacture of Paper and Boards - Deb, D. B. (Indian Forester, 1978)
The present paper On 'Plants used for manufacture of paper and boards' is the seventh of a series of papers on Economic Plants of Tripara State, based on Botanical Survey of the State by the author and study of enormous scientific literature on the subjects concerned, Plants used for manufactures of paper and boards, which are found in the State are discussed in the paper.